Structuri ale intersubiectivității în practicile dialogice - Alexandru COSMESCU (Philologia, 2024)
The concept of dialogic practices is often used in the literature in the absence of an explicit definition. The present paper aims to address this shortcoming. In the first section, dialogic practices are approached from the perspective of embodied discursive interaction, as ways of reorienting the interlocutors, with the help of utterances, towards aspects of the utterances they produce or towards the experience underlying their production. The second section explicates, on the basis of an excerpt from the transcript of a micro-phenomenological interview session, the discursive structure of a dialogic practice, highlighting the following sequence: experiential utterance – reformulation – question. In the third section, five characteristic features of dialogic practices are reviewed from the perspective of the relation between the concepts of form of life and discursive practice: their learned character, consensual character, structured character, demarcated character, autotelic character.